Olfactory Dysfunction in Adults from Rio Grande do Norte: A Cross-Sectional Study - Henrique de Paula Bedaque; Emerson Kennedy Ribeiro de Andrade Filho; Caio de Oliveira Rabelo; José Eduardo Nóbrega Moura; Kelvin Leite Moura; José Diniz Junior; Maria Luisa Nobre Medeiros e Silva Guimarães (International Archives of Otorhinolaryngology, 2024)
Introduction Smell is one of the senses of the human body, and it can be affected by several factors, such as viral infections, traumatic brain injury, iatrogenesis, smoking, and neurodegenerative and systemic diseases.